Systematic review and meta‐analysis of respiratory syncytial virus infection epidemiology in Latin America. (28th November 2013) - Bardach, Ariel; Rey‐Ares, Lucila; Cafferata, María Luisa; Cormick, Gabriela; Romano, Marina; Ruvinsky, Silvina; Savy, Vilma
SUMMARY Respiratory syncytial virus (RSV) is a frequent cause of acute respiratory infection and the most common cause of bronchiolitis in infants. The aim of this systematic review and meta‐analysis was to obtain a comprehensive epidemiological picture of the data available on disease burden, surveillance, and use of resources in Latin America. Pooled estimates are useful for cross‐country comparisons. Data from published studies reporting patients with probable or confirmed RSV infection in medical databases and gray literature were included from 74 studies selected from the 291 initially identified. When considering all countries, the largest pooled percentage RSV in low respiratory tract infection patients was found in the group between 0 and 11 months old, 41.5% (95% CI 32.0–51.4). In all countries, percentages were increasingly lower as older children were included in the analyses. The pooled percentage of RSV in LRTIs in the elderly people was 12.6 (95% CI 4.2–24.6). The percentage of RSV infection in hospitalized newborns was 40.9% (95% CI 28.28–54.34). The pooled case fatality ratio for RSV infection was 1.74% (95% CI 1.2–2.4) in the first 2 years of life. The average length of stay excluding intensive care unit admissions among children with risk factors for severe disease was 12.8 (95% CI 8.9–16.7) days, whereas it averaged 7.3 (95% CI 6.1/8.5) days in otherwise healthy children. We could conclude that infants in their first year of age were the most vulnerable population. To our knowledge, this is the first systematic review on RSV disease burden and use of health resources in Latin America. Copyright © 2013 John Wiley & Sons, Ltd.